Efficient Production of the Flavoring Agent Zingerone and of both (R)- and (S)-Zingerols via Green Fungal Biocatalysis. Comparative Antifungal Activities between Enantiomers - Svetaz, Laura Andrea (2014)
Zingerone (1) and both chiral forms of zingerol (2) were obtained from dehydrozingerone (3) by biotransformation with filamentous fungi. The bioconversion of 3 with A. fumigatus, G. candidum or R. oryzae allowed the production of 1 as the sole product at 8 h and in 81%–90% at 72 h. In turn, A. flavus, A. niger, C. echinulata, M. circinelloides and P. citrinum produced 1 at 8 h, but at 72 h alcohol 2 was obtained as the major product (74%–99%). Among them, A. niger and M. circinelloides led to the anti-Prelog zingerol (R)-2 in only one step with high conversion rates and ee. Instead, C. echinulata and P. citrinum allowed to obtain (S)-2 in only one step, with high conversion rates and ee. Both chiral forms of 2 were tested for antifungal properties against a panel of clinically important fungi, showing that (R)-, but not (S)-2 possessed antifungal activity